POLITIK HUKUM PERADILAN AGAMA DALAM PROSEDUR PENYELESAIAN SENGKETA EKONOMI SYARI’AH - Tanjung, Ardi Akbar; Wahdini, Muhammad (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
The existence of the judiciary for the Muslims is a discretion. The religious courts as litigation institutions have absolute authority. Since the birth of Act No. 3 in 2006, Sharia economic disputes have fallen within the scope of absolute jurisdiction. However, the legislative provisions that have been introduced recently have reduced the authority in question. Based on the Law on Religious Justice and reinforced by the Constitutional Court Decision No. 93 of 2012 has its own advantages and constraints in the exercise of its role. The results of this study show that the Religious Court, in addition to limiting the forms of non-litigation settlement that can be chosen, also constitutes a new norm that the parties are granted rights by means of obstacles which it makes shift the power of the court in the environment of religious justice to power in the general environment of justice. In addition to the settlement of economic disputes of the Shariah: Sources of the Law of Events (Formal Law) and Material Law Sources, consisting of: Regulations of Laws-Laws, Fatwa-fatwa of the National Council of Shari'ah (DSN), Aqad Treaty (Contract), Fiqih and Ushul Fiqich, Customary Habits, and Jurisprudence.